KOMUNIKASI ORGANISASI UBUDIYAH DALAM MENDISIPLINKAN SHALAT BERJAMAAH SANTRI DI PONDOK PESANTREN SUKOREJO - Rizal Rifansyah; Edy Supriyono (Fakultas Dakwah Universitas Ibrahimy, 2026)
This paper discusses the organizational communication of the Ubudiyah Salafiyah Syafi'iyah Islamic Boarding School (Pondok Salafiyah Syafi'iyah) in overseeing the discipline of congregational prayer among male students. Students' discipline in congregational prayer reflects adherence to the school's rules and regulations. However, some students still face obstacles such as laziness after the school holidays and the students' busy daily activities. This research method is a qualitative case study. Data collection used observation and in-depth interviews with administrators and students. The results indicate that the organizational communication strategy implemented by the Ubudiyah Salafiyah Syafi'iyah Islamic Boarding School (Pondok Salafiyah Syafi'iyah) includes a system of lines of instruction and lines of coordination, with the dominant line of coordination communication. First, the organizational communication system consists of establishing communication in monitoring, establishing communication in supervising, establishing communication in maintaining discipline, dress code, time discipline, and implementation discipline. Second, the process communication system is implemented. Third, the coordination communication system is implemented. Fourth, establishing communication between administrators.